The effectiveness of a school-based support team in implementing integrated schools' health policy in a secondary school setting in Mankweng District, Limpopo Province - Rabothata, Mabokoa Allpheus (My University, 2023)
This qualitative case study investigated the effectiveness of a school-based support team in implementing integrated schools’ health policy in a secondary school setting in Mankweng District, Limpopo Province. The three objectives of this study were to develop an in-depth understanding of the nature and role of school-based care and support teams in the basic education sector in Mankweng District, Limpopo Province, and to explore the experiences of schools-based care and support teams in sharing and transferring knowledge in implementing the Integrated Schools Health Policy. Furthermore, to assess how the insights revealed may inform the development of best practice strategies for use by schools-based care and support teams in implementing the Integrated Schools Health Policy in the rural basic education sector in the Mankweng district. A non-probability sample of 15 purposively selected participants was used including five educators, five members of the school-based support teams and five provincial education department officials to gather primary research data. The research data was gathered through the use of face-to-face semi-structured interview. The interviews were audio-recorded and transcribed. Using Tesch’s eight descriptive data analysis technique, the gathered data was analysed. The key findings from the study indicated that school-based support teams in the Mankweng District have not been effective in implementing the integrated schools’ health policy to support learners with reported and disclosed support needs. The recommendations for improving the efficacy of the school-based support teams in the Mankweng District have been provided.
Thesis (MPAM.) -- University of Limpopo, 2023
Keywords: School support team; School health policy implementation; Secondary schools; Mankweng District; Limpopo Province; School support teams; School hygiene; School-based child care